Lycopene inhibits caspase-3 activity and reduces oxidative organ damage in a rat model of thermal injury - ŞENER, GÖKSEL; KAYA, ÖZLEM TUĞÇE; OBA, RABİA; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (ELSEVIER SCI LTD, 2012)
Oxidative stress has been implicated in various pathological processes including burn induced multiple organ damage. This study investigated the effects of lycopene treatment against oxidative injury in rats with thermal trauma. Under ether anesthesia, shaved dorsum of the rats was exposed to 90 degrees C bath for 10 s to induce burn and treated either vehicle (olive oil) or lycopene (50 mg/kg orally). Rats were decapitated 48 h after injury and the tissue samples from lung and kidney were taken for histological analysis and the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO), superoxide dismutase (SOD), catalase (CAT) and caspase-3 activities. Proinflammatory cytokines, TNF-alpha and IL-1 beta, were assayed in blood samples. Severe skin scald injury caused a significant decrease in GSH levels, SOD and CAT activities, and significant increases in MDA levels, MPO and caspase-3 activities of tissues. Similarly, plasma TNF-alpha and IL-1 beta. were elevated in the burn group as compared to the control group. Lycopene treatment reversed all these biochemical indices. According to the findings of the present study, lycopene possesses antiinflammatory, antiapoptotic and antioxidant effects that prevents burn-induced oxidative damage in remote organs. (C) 2012 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Burn; Oxidative stress; Lycopene; Caspase-3; Cytokine; Antioxidant; LIPID-PEROXIDATION; RENAL INJURY; DNA-DAMAGE; BURN; SKIN; PROTECTS; STRESS; INFLAMMATION; MEDIATORS; RADIATION